AN ANALYSIS ON CUSTOMER SATISFACTION, TRUST AND LOYALTY TOWARD ONLINE SHOP (A CASE STUDY OF TOKOPEDIA.COM) - Ayudya Dhiranty; Budi Suharjo; Gendut Suprayitno (Indonesian Journal of Business and Entrepreneurship (IJBE), 2017)
In reference to the results of national research conducted by the Association of Internet Service Providers Indonesia (APJII) in cooperation with PusKaKom UI, the number of internet users (88.1 million) and its penetration (34.9%) in Indonesia has gradually increased. Also, the research identifies the issues of satisfaction, trust and loyalty in online shopping. The presence of actors in e-commerce business benefits the customers to personally choose the site to shop. The strategies to keep customer satisfaction trust and loyalty on one site challenge the actors in the business. In this regard, this paper examines customer satisfaction, trust and loyalty in online shopping in reference to the Quality User Interface (UIQ), Information Quality (IQ), Perceived Security Risk (PSR) and Perceived Privacy (PP) variables with case studies On Tokopedia.com. The study was conducted with 211 respondents by using self-administrated questionnaires in Survey Monkey platform in Jakarta and Bogor. The data were analyzed by using Structural Equation Modeling (SEM). Thus, the results show that the variables of UIQ, IQ, PSR and PP have an influence on satisfaction and trust. The variable of satisfaction has an influence on trust. However, these variables have no direct influence on loyalty.Keywords: e-commerce, satisfaction, trust, loyalty, SEMABSTRAKHasil riset nasional yang dilakukan oleh Asosiasi Penyelenggara Jasa Internet Indonesia (APJII) bekerjasama dengan PusKaKom UI, pengguna internet Indonesia (88.1 juta) dan penetrasinya (34.9%) mengalami peningkatan. Namun, dari riset juga ditemukan bahwa adanya isu-isu kepuasan, kepercayaan dan loyalitas dalam berebelanja online. Adanya banyak pelaku dalam bisnis ecommerce membuat konsumen memiliki keuntungan untuk memilih situs yang menjadi tempat berbelanja. Bagaimana membuat konsumen terpuaskan dan percaya sampai dengan setia pada satu situs menjadi tantangan para pelaku bisnis. Sehubungan dengan hal tersebut, tulisan ini akan meneliti kepuasan, kepercayaan dan loyalitas konsumen dalam berbelanja online yang ditnjau dari variabel User Interface Qualiy (UIQ), Information Quality (IQ), Perceived Security Risk (PSR) dan Perceived Privacy (PP) dengan studi kasus pada Tokopedia.com. Penelitian dilakukan dengan 211 responden menggunakan self-administrated questionnaire dengan platform SurveyMonkey di Jakarta dan Bogor. Analisis data menggunakan Sturctural Equation Modeling (SEM). Hasil menunjukan bahwa variabel UIQ, IQ, PSR dan PP mempunyai pengaruh terhadap kepuasan dan kepercayaan. Variabel kepuasan mempunyai pengaruh terhadap kepercayaan. Namun variable tersebut tidak berpengaruh langsung kepada loyalitas.Kata kunci: ecommerce, kepuasan, kepercayaan, loyalitas, SEM